MENTORING IN PUBLIC MANAGEMENT: CONCEPTUAL AND PRACTICAL APPROACHES AT THE NATIONAL AND INTERNATIONAL LEVEL - VIRGINIA BĂLEANU; SABINA IRIMIE (Annals of the University of Petrosani: Economics)
The paper aims to highlight the important role that mentoring can play for public sector management in general, and for implementing Public Administration Reform in Romania in particular. An extended documentary research of recent international literature and practices that address this topic allowed us to observe a considerable gap relative to the approaches of mentoring in management of other sectors. Moreover, a gap appears also if when comparing the situation of implementing government mentoring programs in European Union countries and in other countries with a more consistent tradition in mentoring such as USA or Canada. Thus, by presenting some conceptual models and programs of reference in the countries last mentioned, our paper tries to contribute in reducing this gap, both at theoretical and practical level.